Changes in the center of pressure of the foot sole during standing-up movement - SAKAMOTO, Miki; TASHIRO, Katsunori; NAKAZAWA, Hitoshi; HARADA, Takashi; UCHI, Masayuki; FUJII, Katsuhito (Journal of exercise physiology, 1991)
The motion of standing up from a chair was analyzed from the viewpoint of the change in the center of pressur(COP)of the foot sole and electromyograms. Anteroposterior movement in COP was prominent. The thigth muscle was seen to play an important role in the standing-up motion, but showed individual variations. It was found that the change in COP was infiluenced by subjects' body height and weight. Standing up with the hands placed on the thigh was easier and more stable than with the hands hung to the sides, with the former showing smaller change in COP. A series of similar muscle activity patterns was observed in subjects' electromyograms. These results suggest that two-dimensional evaluation of the motion of standing up from a chair, one of the basic movements in the activities of daily livings, is useful.